Effects of rate of decrease in power output in decrement-load exercise on oxygen uptake - Yano, T; Yunoki, T; Matsuura, R; Arimitsu, T; Kimura, T (Physiological research, 2007)
The purpose of this study was to examine how oxygen uptake (Vo2) in decrement-load exercise (DLE) is affected by changing rate of decrease in power output. DLE was performed at three different rates of decrease in power output (10, 20 and 30 watts.min(-1): DLE10, DLE20 and DLE30, respectively) from power output corresponding to 90 % of peak Vo2. Vo2 exponentially increased and then decreased, and the rate of its decrease was reduced at low power output. The values of Vo2 in the three DLE tests were not different for the first 2 min despite the difference in power output. The relationship between Vo2 and power output below 50 watts was obtained as a slope to estimate excessive Vo2 (ex-Vo2) above 50 watts. The slopes were 10.0+/-0.9 for DLE10, 9.9+/-0.7 for DLE20 and 10.2+/-1.0 ml.min(-1).watt(-1) for DLE30. The difference between Vo2 estimated from the slope and measured Vo2 was defined as ex-Vo2. The peak value of ex-Vo2 for DLE10 (189+/-116 ml.min(-1)) was significantly greater than those for DLE20 and for DLE30 (93+/-97 and 88+/-34 ml.min(-1)). The difference between Vo2 in DLE and that in incremental-load exercise (ILE) below 50 watts (DeltaVo2) was greater in DLE30 and smallest in DLE10. There were significant differences in DeltaVo2 among the three DLE tests. The values of DeltaVo2 at 30 watts were 283+/-152 for DLE10, 413+/-136 for DLE20 and 483+/-187 ml.min(-1) for DLE30. Thus, a faster rate of decrease in power output resulted in no change of Vo2 at the onset of DLE, smaller ex-Vo2 and greater DeltaVo2. These results suggest that Vo2 is disposed in parallel in each motor unit released from power output or recruited in DLE.
Keywords: Exercise Test; dospělí; Respiratory Mechanics; energetický metabolismus; Humans; Oxygen Consumption; lidé; mužské pohlaví; spotřeba kyslíku; cvičení; Male; Exercise; Energy Metabolism; mechanika dýchání; Adult; oxid uhličitý; Carbon Dioxide; zátěžový test